Employee Performance Development Model Through Organizational Restructuring of Social Media Marketing and Work Engagement - Dingot Hamonangan Ismail; Joko Nugroho; Danang Aziz Akbarona; Aspizain Caniago (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Changes in work dynamics due to the dominance of the digital generation and the increasing use of social media require new strategies to improve employee performance. Based on these conditions, this study aims to analyze the effect of organizational restructuring, social media marketing, and work engagement on employee performance. The study used a descriptive quantitative approach with a survey method of 132 permanent employees at an international certification organization in Jakarta. Data analysis was conducted using partial and simultaneous regression tests to measure the influence of each independent variable on employee performance. The results showed that organizational restructuring, social media marketing, and work engagement partially had a positive and significant effect on employee performance. Simultaneously, the three variables also showed a positive effect with t and F values ​​exceeding the critical value. These findings indicate that employee performance can be improved through strategic restructuring, effective use of social media, and increased work engagement. However, this study was limited to one organization in Jakarta with a cross-sector approach, so the results cannot necessarily be generalized to other sectors or regions. This study provides a practical framework for organizations to improve performance through a modern management approach in the digital era.